The Service Quality Influence and The School Facilities to The Students’ Satisfaction Through The School Reputation As The Intervening Variable - Setiawan, Muh Afrizal; Fakhruddin, Fakhruddin; Kardoyo, Kardoyo (Educational Management, 2020)
Education development nowadays pushes the education foundation to fulfill all the needs of the school members like the teachers, staff, students, and parents. The manner is by increasing the teaching-learning process pleasure through good services. Furthermore, the foundations have to anticipate to face competitive competition. They are responsible to search and increase all the aspects inside. This research is a quantitative approach using path analysis. The sample of this research was 121 students from grade X, XII, and XIII. It was taken by using proportionated stratified random sampling techniques based on the class level in SMK 2 Purnama Semarang. The purpose of this research is to analyze directly and indirectly between the service quality and the school facilities to the students’ satisfaction through the school reputation as the intervening variable. The instrument of collecting the data; It used questionnaires and the observation sheet. The result of the research shows if there is the direct service quality (Sig. 0.046) and the school facilities (Sig. 0.000) influence the school reputation, the direct service quality (Sig. 0.005), the school facilities (Sig. 0.006) and the school reputation (score Z 1.5164) cannot become the influence mediator between the service quality and the school facilities to the students’ satisfaction. The conclusion; there are the service quality direct variable influence and the school facilities to the students' satisfaction. However, the indirect school reputation variable cannot mediate the influence between the service quality and the school facilities to the students' satisfaction.